A multidimensional Framework for Routine Outcome Measurement in Liaison Psychiatry (FROM-LP)†. (August 2016) - Trigwell, Peter; Kustow, James
Summary: In the field of liaison psychiatry, as in all areas of healthcare, there is an essential need for well-organised and consistent collection of information on outcomes, from a range of perspectives. This special article introduces, and describes the development of, the multidimensional Framework for Routine Outcome Measurement in Liaison Psychiatry (FROM-LP). This was challenging owing to the variety of service settings and types of intervention which characterise liaison psychiatry. Similar challenges may be faced by other specialties and this, along with the direct relevance of much of the eventual content of the framework, will broaden the interest of this article.